Comparison of instruments for screening frailty in community-dwelling older adults - Martins , Andréia Christiane Amâncio; Santos , Brenda Gomes dos; Santiago , Marianne Caldeira de Faria; Boitrago , Sarah Caroline Oliveira de Souza; Costa , Fernanda Marques da; Carneiro , Jair Almeida (Seven Editora, 2024)
Objective: To conduct a systematic review of studies that verify the comparison between frailty assessment instruments. Methods: Systematic review conducted between January and March 2023 in an electronic database (LILACS and MEDLINE). For the construction of the search strategies, an adaptation of the acronym PICO was used, where P = population (community-dwelling elderly), I: phenomenon of interest (comparison of frailty by different instruments) and CO = context (Primary Health Care). In the searches, the terms "elderly" AND "fragility" AND "instruments" and "Elderly" AND "fragility" AND "instrument" were considered, and the final selection resulted in 13 articles.  Results: The comparison between the Edmonton Frailty Scale (EFS) and the Clinical Functional Vulnerability Index (IVCF-20) showed moderate agreement and a strong positive correlation. However, the prevalence of frailty was discrepant, being higher when EFE was used. When analyzing the agreement between the Subjective Assessment of Frailty (SFA) and the IVCF-20, the results indicated weak agreement in the classification of frailty between these instruments. However, moderate agreement was found when the outcome was dichotomized into "frail" and "non-frail". Despite evaluating similar concepts, SFA and IVCF-20 are complementary and one cannot replace the other. Conclusions: Although several studies address different frailty assessment instruments, there is still a scarcity of studies investigating the agreement between these instruments and, in addition, the results presented reinforce the need for a standardized instrument to measure frailty in the elderly in Primary Health Care. DOI:https://doi.org/10.56238/sevened2024.007-095